2019
DOI: 10.1080/15592294.2019.1625674
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting DNA methylation responses of inbred fish lines to different rearing environments

Abstract: Epigenetic mechanisms generate plastic phenotypes that can become locally adapted across environments. Disentangling genomic from epigenomic variation is challenging in sexual species due to genetic variation among individuals, but it is easier in self-fertilizing species. We analysed DNA methylation patterns of two highly inbred strains of a naturally self-fertilizing fish reared in two contrasting environments to investigate the obligatory (genotype-dependent), facilitated (partially depend on the genotype) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 61 publications
(85 reference statements)
1
29
0
Order By: Relevance
“…Despite this topic being almost unexplored, Berbel‐Filho et al . () recently analysed the DNAm patterns of two highly inbred strains of a naturally self‐fertilising fish reared in two contrasting environments, in order to understand the obligatory (genotype dependent), facilitated (partially genotype dependent) or pure (genotype independent) nature of epigenetic variation. Their results showed higher methylation differences between genotypes than between environments, suggesting that in some cases genotypes have an overriding influence on DNAm patterns.…”
Section: Incorporating Epigenetic Biomarkers/data Into Eramentioning
confidence: 99%
“…Despite this topic being almost unexplored, Berbel‐Filho et al . () recently analysed the DNAm patterns of two highly inbred strains of a naturally self‐fertilising fish reared in two contrasting environments, in order to understand the obligatory (genotype dependent), facilitated (partially genotype dependent) or pure (genotype independent) nature of epigenetic variation. Their results showed higher methylation differences between genotypes than between environments, suggesting that in some cases genotypes have an overriding influence on DNAm patterns.…”
Section: Incorporating Epigenetic Biomarkers/data Into Eramentioning
confidence: 99%
“…Using data from all sampling sites, we found that genome‐wide DNA methylation was strongly influenced by selfing lineage, and only at a smaller scale by inbreeding through its interaction with selfing lineage (Bell et al, ; Bjornsson et al, ; Dubin et al, ; Gertz et al, ). Strong epigenetic differences between selfing lines had been identified previously in K. marmoratus (Berbel‐Filho et al, ; Ellison et al, ), indicating an important role of the genetic background in the epigenetic variation of mangrove killifishes. In addition, we also found a significant correlation between DNA methylation and genetic variation (at both AFLP and microsatellites data), suggesting that autonomous variation in DNA methylation may be limited (Dubin et al, ).…”
Section: Discussionmentioning
confidence: 66%
“…DNA methylation is the best characterized epigenetic modification (Lea, Vilgalys, Durst, & Tung, ) and has important roles on pretranscriptional control in several biological processes, such as cell differentiation and genomic imprinting (Koch et al, ). Variation in DNA methylation is not completely independent from the genome, and epialleles can have different degrees of autonomy from the genotype (Berbel‐Filho, Rodríguez‐Barreto, Berry, Garcia de Leaniz & Consuegra, ; Richards ; Dubin et al, ; Leung, Breton, & Angers, ). In addition, in some plants and animals, individuals with low levels of heterozygosity display high levels of genome‐wide DNA methylation variation (Liebl, Schrey, Richards, & Martin, ; Richards, Schrey, & Pigliucci, ; Schrey et al, ), suggesting that DNA methylation could contribute to the adaptation of organisms with limited genetic diversity to environmental change (Castonguay & Angers, ; Douhovnikoff & Dodd, ; Liebl et al, ; Schrey et al, ; Verhoeven & Preite, ).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of CpG covered in the RR genome reached 6.1% of the total number of genomic CpGs, which was similar to mouse and zebrafish (7.0% and 5.3%, respectively, (Chatterjee et al, 2013)), but higher than what other studies reported for diverse fish species such as stickleback [1% (Metzger & Schulte, 2017)], Atlantic salmon [2.75% (Uren Webster et al, 2018)], rainbow trout [<1% (Baerwald et al, 2016)] and guppies [1.5-2% (Hu et al, 2018)]. In mangrove rivulus brain, Berbel-Filho et al (Berbel-Filho et al, 2019b) also reported a lower CpG coverage at 1.2%. This is surprising considering that different tissues of the same species usually show the same methylation profile (Zhang, Hoshida, & Sadler, 2016), and methodological aspects can not be rejected to explain this discrepancy.…”
Section: Characterization Of the Mangrove Rivulus Rr Genomementioning
confidence: 61%